Analisis Kesulitan Belajar Operasi Hitung Perkalian Dan Pembagian Pecahan Di SD Islam Plus Masyithoh Kroya - Naeli Nur Hidayah (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2025)
This study aims to identify the learning difficulties of students in mathematics learning at SD Islam Plus Masyitoh Kroya. The research was conducted by gathering data sources through a case study writing method using qualitative research. Based on the results or data obtained through observations and interviews in the 6th grade, the author found that students experienced learning difficulties in mathematics learning, particularly in the material of multiplication and division of fractions. The main cause of the students' learning difficulties is the lack of understanding of fraction concepts and operations with whole numbers such as multiplication and division. As a result, students tend to make mistakes in solving problems related to the multiplication and division of fractions. In addition, low motivation and interest in learning also affect students' understanding of mathematics material. Most students who experience learning difficulties are not interested in mathematics subjects; they consider learning mathematics very difficult, often confusing, with a large number of formulas to be used, and students generally do not enjoy calculations. Therefore, a more engaging, interactive, and contextual learning approach and tutoring activities are needed to improve students' conceptual understanding, interest, and motivation in learning mathematics